Digital agency in agricultural knowledge systems: Fostering responsible co-development of digital technical advisory tools - McCampbell, Mariette (2025)
Presented by Mariette McCampbell, Inclusive Digital Tools Project of Agroecological TRANSITIONS, at the “Increasing farmer’s digital agency for agroecology” webinar on 8 May 2025, an event of the Transformative Partnership Platform (TPP) for Agroecology and Agroecological TRANSITIONS Project (ATDT).